Obligacje komunalne czy kredyt bankowy - kalkulacje kosztu kapitału - Kozuń-Cieślak, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Local government entities have been entitled to incur a debt on the capital market. In the paper the attention has been focused on the problem of capital cost calculations. The paper shows a method of true interest cost calculations (TIC) and a case study of TIC calculations for debt incurred by bonds issuing or a bank credit. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 541-548